2006
DOI: 10.1111/j.1460-9592.2005.01827.x
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol vs morphine during adenotonsillectomy for obstructive sleep apnea in children

Abstract: Tramadol may be a suitable drug for children undergoing adenotonsillectomy for OSA. Further work is required to investigate this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…When compared with morphine, tramadol was shown to result in fewer respiratory events post-tonsillectomy 36 ; however, further work is required to assess the safety of tramadol as an alternative analgesic. A retrospective review identified a reduction in recurrent hypoxemia after adenotonsillectomy in children who have severe OSA resulting from dexamethasone administration (∼2.4 mg/kg) and a reduction opioid dose.…”
Section: Figurementioning
confidence: 99%
“…When compared with morphine, tramadol was shown to result in fewer respiratory events post-tonsillectomy 36 ; however, further work is required to assess the safety of tramadol as an alternative analgesic. A retrospective review identified a reduction in recurrent hypoxemia after adenotonsillectomy in children who have severe OSA resulting from dexamethasone administration (∼2.4 mg/kg) and a reduction opioid dose.…”
Section: Figurementioning
confidence: 99%
“…[2][3][4][5][6] Tramadol, a racemic opioid widely used for mild to moderately severe acute pain management, has been proposed as an alternative to codeine because it is thought to be associated with decreased postoperative sedation and respiratory depression. 7 Tramadol is extensively metabolized in the liver by the cytochrome P450 monooxygenases followed by conjugation reactions producing inactive glucuronides and sulfates (for details, https://www.pharmgkb.org/ pathway/PA165946349). Its main analgesic metabolite (M1) results from the O-demethylation catalyzed by the cytochrome P450 CYP2D6.…”
mentioning
confidence: 99%
“…This study was a single-dose RCT examining the effectiveness of intravenous (IV) tramadol versus IV morphine following adenotonsillectomy in 66 pediatric patients 1 to 8 years old. 11 The RR of patients experiencing at least 1 desaturation episode was 1.63 times greater in patients who received morphine as compared to patients who received tramadol (95% CI: 0.64-6.13). An additional study by Zhuang and colleagues 12 reported no difference in the incidence of respiratory depression between patients receiving postoperative IV dexmedetomidine or IV morphine (p=0.85).…”
Section: Resultsmentioning
confidence: 99%